Developing Supplementary English Materials Through Youtube Platform - Amaliah, Amaliah; Widodo, J. Priyanto; Musyarofah, Lailatul (Jurnal Basicedu, 2022)
In the hybrid learning era, teachers increasingly need flexible and digital materials. Learning process is now conditioned as a need of students to develop their life skills. This process is carried out by teachers, students, parents, related parties, such as media, and the community. However, Â not all the materials in the form of videos of learning are available and can be found easily on the internet. The purpose of this research is developing English supplementary materials for grade nine through YouTube platform based on the content, audio, and visual performance. Research & Development (R&D) Model was applied in this research. The findings of the research are the four revisions of the supplementary materials in the ninth grade through YouTube platform: (1)product: there is revision of the content especially for understandable aspect, that is a translation subtitle through YouTube for the content of supplementary materials, (2) lesson plan: some teachers suggest to makeÂ  the lesson plan available to accompany and guide them to teach, the writer make and give the lesson plan which used for accompanying the products which can be used, adapted, based on the students characteristics in each school, (3) modul as a systematic written book with simple explanation to make students learn independently is also required, (4) operational direction: the revision of operational direction is conducted by revising the description of supplementary materials which covers direction of learning, exercise and questions related to the supplementary materials.